2010
DOI: 10.1007/s11999-010-1283-y
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic Evaluation of Chronic Radial Head Dislocation: Three-dimensional and Quantitative Analyses

Abstract: Level III, prognostic study. See Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…The radial head as well as the radial notch of the proximal ulna should be analyzed both for surgical indication and for planning in long-standing cases. 3,19 In this case, the radial head showed a normal concave appearance, but the radial notch of the proximal ulna was shallow. Therefore, notchplasty was a prerequisite for reduction of the radial head.…”
Section: Figurementioning
confidence: 71%
See 1 more Smart Citation
“…The radial head as well as the radial notch of the proximal ulna should be analyzed both for surgical indication and for planning in long-standing cases. 3,19 In this case, the radial head showed a normal concave appearance, but the radial notch of the proximal ulna was shallow. Therefore, notchplasty was a prerequisite for reduction of the radial head.…”
Section: Figurementioning
confidence: 71%
“…18 Although the radial shaft showed no deformity, the radial head showed slight enlargement but otherwise normal concave appearance. 19 The ulna had deformities of 11°extension, 6°v algus, and 8°external rotation, as well as 10 mm shortening (Fig. 2).…”
Section: Case Reportmentioning
confidence: 98%
“…6 On MRI, we observed the radial notch of the ulna on the anterior-lateral side of the ulna instead of the lateral side, which has been described for chronic radial head dislocation. 17 The radial notch of the ulna was covered with cartilage. This finding suggested that the abnormal proximal radioulnar joint may have been responsible for the dislocation of the radial head.…”
Section: Discussionmentioning
confidence: 99%
“…1). The distance of COR translation during forearm rotation also was investigated on Plane P. The distance along the line passing through the posterior border of the ulna and the tip of the coronoid process [28] and the distance along the perpendicular to that line were calculated as the distance of sagittal translation of the COR (d-S) and the distance of coronal translation of the COR (d-C), respectively.…”
Section: Methodsmentioning
confidence: 99%